Investigating Pre-Financial Close Risks Associated with Communal Land Ownership Rights in Onshore Wind Energy Development in South Africa - Mokone, Bothokgami (Energy Research Centre, 2021)
There are challenges to be addressed if South Africa is to reach its full potential in exploiting wind energy resources. One of such challenges is communal land ownership, which is used for the development of wind energy in rural areas. Often, communal lands have no formal land structures, ownership or title deeds to support the individuals and communities that claim possession thereof. This challenge of communal land ownership and the associated risks impact upon investments by independent power producers in wind energy infrastructure. Land in South Africa remains a highly sensitive issue given the historical injustice of land dispossession which became the source of poverty and inequality. Moreover, transitioning to renewable energy sources would add more pressure on land scarcity. Commercial wind energy projects are capital intensive, with high annual turnovers. Achieving financial close is a risk mitigation strategy that confirms that early-stage contractual agreements have been reached in the development stage of a wind project lifecycle. Therefore, risk identification and allocation are fundamental to ensuring that the structuring and contractual obligations of non-recourse project financing are met. Wind energy plants require significant stretches of land, and this is progressing at an industrial scale and often, onshore wind energy projects are located in rural areas, thereby impacting local communities. Land ownership rights are a key element for communities, in which renewable energy development takes place. Households living on communal land, of which the right to use land is vested in individual households, are situated on such lands. This study uses the theory of risk management to investigate pre-financial close risks in developing wind energy associated with communal land ownership rights and the extent to which those risks inhibit wind energy projects from reaching financial close in South Africa. An exploratory research design was applied, while a questionnaire survey was used to collect data from wind developers. The study identified the pre-financial close risks associated with communal land to be technical, legal, economic, social and political risks. Indeed, there is a lack of clear, long-term policy framework to support investments in clean energy infrastructure. This causes significant delays to wind energy project development and it negatively affects financial close. In addition, there are competing interests among multiple stakeholders, leading to the burdensome processes involved in securing leasehold agreements on communal land. As a result, projects which were initially proposed on communal land, have not always reach financial close as planned while others were stopped. The results show that risk mitigation tools could include effective and continuous stakeholder management which is critical to reaching financial close. Furthermore, the Department of Rural Development and Land Reform has not established a streamlined process that developers can follow to secure communal land leasehold rights, given that the process is time-consuming.